1995
DOI: 10.1016/s0266-7681(05)80137-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Infection Following Hand Surgery

Abstract: An audit was designed to analyse the risk factors for developing post-operative wound infection following hand surgery. 249 consecutive patients were prospectively entered into the study. 236 (95%) patients were available for follow-up. Infection was diagnosed by clinical criteria. There was an infection rate of 10.7% in elective operations and 9.7% in emergency operations. There was no significant reduction in infection rate in the elective group with the use of antibiotics (P = 0.5). In the emergency group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 25 publications
2
59
1
4
Order By: Relevance
“…1 The benefits of 'daycase surgery' include a greatly reduced rate of infection, reported as low as 2% in elective orthopaedics and hand surgery 2 although another study reported a much higher 10% infection rate. 3 The present study has shown that very low rates of postoperative infection can be expected in elective hand surgery, and that this is probably due to seniority of surgeon, operative technique, short duration of operation, 4,5 and close postoperative follow-up. Wearing of sterile gowns, face-masks, and laminar airflow seem to have little effect in day-case hand surgery.…”
Section: Discussionmentioning
confidence: 58%
“…1 The benefits of 'daycase surgery' include a greatly reduced rate of infection, reported as low as 2% in elective orthopaedics and hand surgery 2 although another study reported a much higher 10% infection rate. 3 The present study has shown that very low rates of postoperative infection can be expected in elective hand surgery, and that this is probably due to seniority of surgeon, operative technique, short duration of operation, 4,5 and close postoperative follow-up. Wearing of sterile gowns, face-masks, and laminar airflow seem to have little effect in day-case hand surgery.…”
Section: Discussionmentioning
confidence: 58%
“…They concluded that debridement and conscientious wound control rather than antibiotics were key points to minimize infection [1]. Swanson, Platt and Page noticed an increased infection rate in contaminated hand wounds, responsive to antibiotics [9,14]. Intravenous flucloxacillin appeared to reduce the rate of postoperative stiffness at a very significant level in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Staphylococcus species are the most common organisms found on the skin of the hand [8,10]. Platt and Page managed to reduce the infection rate in hand injuries with perioperative antibiotics [9]. In our study, no case of infection was documented and of the cases who had received intravenous flucloxacillin none developed stiffness.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, the Joint Commission's Surgical Care Improvement Project has issued a list of procedure-specific prophylactic antibiotics. Studies have shown that compliance with these guidelines varies across institutions and procedures and regimens not in compliance have involved both undertreated and over treated cohorts [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%